Sustainable Agricultural Development in the Southeast Region of Romania - Daniela Lavinia Balasan; Florin Marian Buhociu (Journal of Agriculture and Rural Development Studies, 2025)
The Southeast Region of Romania, which includes the counties of Constanța, Tulcea, Brăila, Buzău, Vrancea, and Galați, represents an area with a strong agricultural sector that is essential for the local economy. Agriculture is an essential sector of the economy in the region, especially due to fertile land and a long-standing tradition in cereal, legume, and sunflower cultivation, as well as livestock farming. The Southeast region of Romania plays an important role in national agricultural production, contributing significantly to wheat, corn, and sunflower crops. In the context of an increasingly volatile global economic climate, sustainable agricultural development and technological modernization have become imperatives for ensuring a prosperous and environmentally friendly future for the region.